(untitled) (Research, Society and Development, 2021)
Babesiosis is a zoonosis caused by different species of Babesia protozoa, which live inside the blood cells. Transmitted by ixodid ticks, it can affect both domestic and wild animals. In the Central-West Region, although there are already descriptions of this hemoparasitosis, little is known about its occurrence, and most studies refer to its detection through molecular diagnostics. Despite this, blood smear is a fundamental diagnostic method, mainly because it is a viable, highly conclusive and low-cost screening test. This study aimed to emphasize the importance of blood smear as a diagnosis for the disease. It was collected data on Babesia spp. findings in blood smears from the HOVET – UFMT routine, during the period of twelve months, and also searched for the existence of a hematological profile, aiming to validate the suspicion even in cases of low parasitemia. 5.333 canine hemograms were processed, of these, those that presented the Babesia spp. trophozoite in the smear cytology, were submitted to an exam evaluation. It was found that even in cases where the cytology results negative, with the clinical history associated to the hematological profile, it is possible to validate the suspicion of the hemoparasitosis. It was found a 0,3% occurrence of babesiosis in dogs, being mostly sporadic findings. The main hematological findings were anemia (68,75%) normocytic normochromic (45,45%), thrombocytopenia (87,5%), leukopenia (75%), eosinopenia (68,75%), lymphopenia (87,5%) and monocytosis (18,75%).